PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DAN MOTIVASI BELAJAR TERHADAP PENGUASAAN KONSEP MELALUI KEMAMPUAN PEMECAHAN MASALAH - Fitri; Walukow, Auldry F.; triwiyono, triwiyono (Papua Journal of Physics Education, 2024)
Research has been conducted with the aims to know: the increase and comparison of direct influence and total influence between PBL model and learning motivation to master the concept of learners through problem solving ability. The method used is pre-experimental design and the descriptions used are one-group pretest-posttest design. The study was conducted at SMP Negeri 2 Jayapura academic year 2017/2018. Population amounted to 245 students class VIII. The sample of the study was class VIII F with sample size of 39 students. The analysis technique used is n-gain analysis and path analysis with two-lane analysis. The results obtained from the data in this study are: 1) There is an increase in the mastery of the concept of physical science IPA in class VIII F SMP Negeri 2 Jayapura is equal to 0.80, 2) Direct influence PBL model on the mastery of the concept that is equal to 26,01% total through the problem solving ability that is 88,2% is the strongest influence, followed by the influence of extrinsic learning motivation on the concept of mastery that is equal to 26,22% and total influence through problem solving ability that is equal to 83,9%, and the influence of intrinsic learning motivation to mastery of concept that is equal to 28,41% and total influence through problem solving ability 79%.